2014
DOI: 10.1002/jat.3015
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic cytotoxicity and DNA strand breaks in cells and plasmid DNA exposed to uranyl acetate and ultraviolet radiation

Abstract: Depleted uranium (DU) has a chemical toxicity that is independent of its radioactivity. The purpose of this study was to explore the photoactivation of uranyl ion by ultraviolet (UV) radiation as a chemical mechanism of uranium genotoxicity. The ability of UVB (302 nm) and UVA (368 nm) radiation to photoactivate uranyl ion to produce single strand breaks was measured in pBR322 plasmid DNA, and the presence of adducts and apurinic/apyrimidinic sites that could be converted to single strand breaks by heat and pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…In cells, uranium causes DNA damage and mutations (Stearns et al, 2005; Coryell and Stearns, 2006; Knobel et al, 2006; Wilson et al, 2014) and we find evidence for strand break in response to 10 μM UA in normal human keratinocytes. Uranium has been shown to cause DNA adducts and strand breaks in the presence of ascorbate (Wilson et al, 2014) and potentiate UV-induced strand breaks through a mechanism involving photoactivation of the uranyl ion (George et al, 2011; Wilson et al, 2015). In addition to these mechanisms, we find that low, non-cytotoxic concentrations of UA inhibit DNA repair and enhance UVR-induced DNA damage indicating that uranium may act as a co-carcinogen when combined with other DNA damaging insults.…”
Section: Discussionmentioning
confidence: 99%
“…In cells, uranium causes DNA damage and mutations (Stearns et al, 2005; Coryell and Stearns, 2006; Knobel et al, 2006; Wilson et al, 2014) and we find evidence for strand break in response to 10 μM UA in normal human keratinocytes. Uranium has been shown to cause DNA adducts and strand breaks in the presence of ascorbate (Wilson et al, 2014) and potentiate UV-induced strand breaks through a mechanism involving photoactivation of the uranyl ion (George et al, 2011; Wilson et al, 2015). In addition to these mechanisms, we find that low, non-cytotoxic concentrations of UA inhibit DNA repair and enhance UVR-induced DNA damage indicating that uranium may act as a co-carcinogen when combined with other DNA damaging insults.…”
Section: Discussionmentioning
confidence: 99%
“…The alkaline version of comet assay is capable to detect various lesions, such as single and/or double stranded, apurinic sites, the oxidative damage in genetic materials [18] even at low IR doses (e.g. -25 cGy) [19].…”
Section: Dna Damage Profile In Peripheral Blood Lymphocytes Of Ir Expmentioning
confidence: 99%
“…Therefore, it is important to determine cellular responses to uranium-induced toxicity at more environmentally relevant concentrations ranging from 50 – 300 μM or 12 – 72 ppm U. Several studies have shown that uranium is not genotoxic at this lower concentration range and activates cellular stress responses rather than cell-mediated death responses (Wilson 2015, Guéguen 2015, Garmash 2014).…”
Section: Introductionmentioning
confidence: 99%